Metal Materials Processes and Manufacturing : 3rd International Conference on Metal Material Processes and Manufacturing (ICMMPM 2020) : selected, peer-reviewed papers from the 2020 3rd International Conference on Metal Material Processes and Manufacturing (ICMMPM 2020), June 22-23, 2020, Singapore, Singapore - Jung, Dong Won (Materials science forum ;)
3rd International Conference on Metal Material Processes and Manufacturing (ICMMPM 2020) Selected, peer-reviewed papers from the 2020 3rd International Conference on Metal Material Processes and Manufacturing (ICMMPM 2020), June 22-23, 2020, Singapore, Singapore.